Efektivitas Pendidikan Kesehatan Reproduksi dengan Media Audio Visual terhadap Pengetahuan Remaja tentang Sexual Harassment di SMKN 1 Kota Dumai - Afni Handayani; Mitra Mitra; Yesica Devis; Emy Leonita; Hastuti Marlina (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2022)
Sexual harassment often occurs among teenagers. They ranged from mild to severe forms such as whistling to rape. UNICEF data in 2019 recorded ten teenagers worldwide experiencing sexual harassment. This research aims to determine the effectiveness of reproductive health education through audio-visual media and leaflet media adolescent knowledge about sexual harassment at SMKN 1 Dumai City in 2021. This study was a quantitative study with a quasi-experimental design. The sample was 120 teenagers and was taken by simple random sampling. Data were analyzed by using the Friedman test. The study's results showed that the audio-visual group had an average value of knowledge before being given counseling. After being given counseling, the value of knowledge increased to 24.0, on the third day respondents' knowledge again decreased to 19.4. Friedman's statistical test results show a p-value=0.000 which means that the use of audio-visual media is effective on adolescent knowledge. Hoped that SMKN 1 Dumai will provide information about sexual harassment through social media so that the data obtained by teenagers are more attached and teenagers can take precautions and take action when experiencing sexual harassment.